2013
DOI: 10.1021/es304659r
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Profiles of Urinary p-Hydroxybenzoic Acid and its Esters (Parabens) in Children and Adults from the United States and China

Abstract: Hydroxybenzoic acid esters (parabens) are used as preservatives in foods, cosmetics, and pharmaceuticals, which results in the exposure of humans to these compounds. Parabens and its metabolite, p-hydroxybenzoic acid (p-HB) are excreted from urine in free and conjugated forms. In this study, free and total forms (free plus conjugated) of parabens and their common metabolite, p-HB, were measured in urine samples collected from U.S. children (n = 40), Chinese children (n = 70), and Chinese adults (n = 26). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(54 citation statements)
references
References 40 publications
5
46
2
1
Order By: Relevance
“…These exposures likely originate from consumer products; therefore, the associations may have important implications across populations. Mean triclosan and paraben levels were similar to those reported in other studies of U.S. children, [23][24][25] but triclosan was more frequently detected in these U.S. children than in Norwegian children. 18 Because these chemicals are nonpersistent in the body, urine concentrations are reflective of exposure at a single time.…”
Section: Discussionsupporting
confidence: 87%
“…These exposures likely originate from consumer products; therefore, the associations may have important implications across populations. Mean triclosan and paraben levels were similar to those reported in other studies of U.S. children, [23][24][25] but triclosan was more frequently detected in these U.S. children than in Norwegian children. 18 Because these chemicals are nonpersistent in the body, urine concentrations are reflective of exposure at a single time.…”
Section: Discussionsupporting
confidence: 87%
“…Because p-hydroxybenzoic acid is a non-specific metabolite common to all parabens, human biomonitoring studies have focussed on analyzing the specific parabens (after hydrolysis) in urine as biomarkers of internal exposure (Ye et al, 2006;Moos et al, 2014). Recent biomonitoring studies have shown that these parabens are ubiquitously present in urine samples from the general population and various sub-populations (Ma et al, 2013;Asimakopoulos et al, 2014;Frederiksen et al, 2010Frederiksen et al, , 2013Frederiksen et al, , 2014CDC, 2015;Calafat et al, 2010;Casas et al, 2011;Philippat et al, 2012;Dewalque et al, 2014;Wang et al, 2013;Shirai et al, 2013;Kang et al, 2013;Meeker et al, 2013).…”
Section: G Modelmentioning
confidence: 99%
“…The presence of parabens in urine samples from Spain and Denmark also was documented Frederiksen et al, 2011). Studies have reported the occurrence of parabens in human plasma, serum, and milk at concentrations on the order of a few nanograms per milliliter (Frederiksen et al, 2011;Schlumpf et al, 2010;Wang et al, 2013;Ye et al, 2008). Nevertheless, information on the occurrence of parabens in foodstuffs and other source of human exposure is still scarce.…”
Section: Introductionmentioning
confidence: 99%